Damage Atlas for Photographic materials - Kristel Van Camp (CeROArt : Conservation, Exposition, Restauration d'Objets d'Art)
In order to rescue a damaged photographic object, preventive or conservative actions are needed. Knowing the specific characteristics of different types of damage is crucial. A damage atlas can provide these characteristics. With this atlas the damage can be recognised and appropriate actions can be taken. This damage atlas offers a first attempt to such a characterisation in the field of photography. The damage atlas contains images and the necessary information about damage on photographic material. The atlas with special annotations about the terminology and the grade of the damage is meant for everybody who works with photographic material, as well in museums as in archives.